Study of reinforced concrete circular column crack control and modifcation in P-M interaction diagram - Eswaran, R.; Sivakumar, S. (Journal of Structural Engineering, 2024)
This paper presents the study of design methods for checking of Reinforced Cement Concrete (RCC) circular columns crack width control. The various case studies of design explain the importance of crack width control in addition to design for limit state of collapse ie., strength requirements. In the beginning, this paper explains the cases for which the higher area of reinforcement is required for crack width control than the requirement for strength aspect. The sample design calculation for crack width checking is also presented. Next, this paper explains the safe zone in P-M interaction curve as per SP-16 of Indian standards, where the circular sections are safe in both strength as well as crack width control requirements. The unsafe zone in P-M interaction curve describes the circular sections are safe as per strength but unsafe as per crack width control requirements. Finally the method for modification of P-M interaction curve in unsafe zone is explained by increasing the percentage of reinforcement to satisfy the crack width control. The modified design charts for calculating area of reinforcement required are presented. These modified design charts provide guidance to the structural designer while designing for limit state of serviceability for RCC circular columns.